Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection - Jadaun, Pratiksha; Shah, Prachibahen; Harshithkumar, R.; Said, Madhukar S.; Bhoite, Shubhangi P.; Bokuri, Sowmya; Ravindran, Selvan; Mishra, Neetu; Mukherjee, Anupam (BMC Complementary Medicine and Therapies, 2023)
Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (HR-ESI-MS) technique, followed by the investigation of their potential as anti-HIV-1 and antioxidant agents through in vitro mechanistic assays. The anti-HIV-1 activity was examined in TZM-bl cells through luciferase gene assay against two different clades of HIV-1 strains, whereas the intracellular ROS generation was analyzed by Fluorescence-Activated Cell Sorting. Additionally, the mechanisms of action of these phyto-extracts were determined through the Time-of-addition assay. The characterization of Carica papaya Linn and Psidium guajava leaves extract through HR-ESI-MS fragmentation showed high enrichment of various alkaloids, glycosides, lipids, phenolic compounds, terpenes, and fatty acids like bioactive constituents. Both the phyto-extracts were found to be less toxic and exhibited potent antiviral activity against HIV-1 strains. Furthermore, the phyto-extracts also showed a decreased intracellular ROS in HIV-1 infected cells due to their high antioxidant potential. Overall, our study suggests the anti-HIV-1 potential of Carica papaya Linn and Psidium guajava leaves extract due to the synergistic action of multiple bioactive constituents.
Keywords: anti-HIV-1 activity; Anti-retroviral; Bioactive constituents; Carica papaya Linn; Cytotoxicity; HR-ESI-MS; Psidium guajava; reactive oxygen species

Mitochondrial resilience and antioxidant defence against HIV-1: unveiling the power of Asparagus racemosus extracts and Shatavarin IV - Jadaun, Pratiksha; Harshithkumar, R.; Seniya, Chandrabhan; Gaikwad, Shraddha Y.; Bhoite, Shubhangi P.; Chandane-Tak, Madhuri; Borse, Swapnil; Chavan-Gautam, Preeti; Tillu, Girish; Mukherjee, Anupam (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: IN-SILICO; INHIBIT HIV-1